Steam-Based Science Module to Optimize Critical Thinking Skills of Grade V Elementary School Students - Sujaryanto, Eko; Sarwanto, Sarwanto; Yulisetiani, Septi (Universitas Sebelas Maret, 2025)
Developing critical skills of fifth-grade elementary school students in Natural and Social Sciences (IPAS) is crucial for 21st-century education, and STEAM offers a contextual approach to address the lack of higher-order skills in current practice. This study aims to: (1) identify the need to develop a STEAM-based IPAS teaching module, (2) design a STEAM-based IPAS teaching module that suits the characteristics of elementary school students, and (3) produce an initial product of the teaching module that is validated by experts. This study uses the R&D (Research and Development) model from Borg and Gall which is simplified into three stages by Sukmadinata, namely preliminary study, model development, and model testing. This article focuses on the preliminary study and initial product development of the module. Data were obtained through literature studies, interviews, observations and document analysis. The development results produced a STEAM-based IPAS module design which was then validated by material experts, media experts, and linguists. The validation results indicate that the module meets the feasibility for use in fifth-grade elementary school IPAS learning. The developed module is ready for use in a limited trial phase in further research.